Resources and Capabilities of the Department of Veterans Affairs to Provide Timely and Accessible Care to Veterans - Health, RAND (RAND Corporation, 2015)
The Department of Veterans Affairs (VA) provides timely and high-quality care to most of its patients, but there are inconsistencies in performance across VA facilities and barriers to effective use of VA resources and capabilities. VA will require more capacity to meet an increase in patient demand in the next five years. Options for increasing capacity include accelerated hiring, full nurse practice authority, and expanded use of telehealth.